Comparing the Effects of Butyric Acid Source and Level on Growth Performance of Nursery Pigs - K. M. Gourley; J. C. Woodworth; J. M. DeRouchey; M. D. Tokach; R. D. Goodband; S. S. Dritz (Kansas Agricultural Experiment Station Research Reports, 2016)
A total of 398 pigs (PIC 19 × 1050 or PIC 3 × C29, initially 13.56 ± 0.02 lb) were used in a 42-d growth study to compare the effects of increasing two different sources of encapsulated butyric acid on growth performance of nursery pigs fed meal diets. Dietary treatments were arranged as a 2 × 2 + 1 factorial with main effects of butyric acid source (ButiPEARL vs. ButiPEARLZ; Kemin Industries, Des Moines, IA) and level (low (1 or 1.38 lb/ton) vs. high (2 or 2.76 lb/ton) respectively) plus a control diet without any butyric acid. The inclusion rates of each product were established such that the same amount of butyric acid was contributed from each source for the low or high levels, respectively. Experimental diets were fed in three phases from d 0 to 7, 7 to 21, and 21 to 42. Pens of pigs (6 barrows and 4 gilts) were balanced by initial BW and randomly allotted to treatments, with 8 replications (pens) per treatment. From d 0 to 7, a source × level interaction (P<0.05) was observed for ADG, ADFI, and F/G, with pigs fed diets containing ButiPEARL having improved performance at the low inclusion, but with those fed high butyric acid not different from the control. However, pigs fed ButiPEARLZ had poorer growth performance at the low level, with the high level having performance similar to the control. In Phase 2 (d 7 to 21), ADG and ADFI were not influenced by butyric acid source or level, but an interaction (P = 0.001) was observed for F/G as pigs fed ButiPEARL had poorer F/G as level increased; whereas pigs fed increasing ButiPEARLZ had improved F/G. For Phase 3 (d 21 to 42), increasing either butyric acid source tended (P = 0.060) to decrease ADG. Overall (d 0 to 42), butyric acid source or level did not affect ADG, ADFI or F/G. In conclusion, this study showed that pigs fed low ButiPEARL in Phase 1 (d 0 to 7) had improved growth performance compared to other treatments with only minor treatment effects observed thereafter. More research is warranted to determine if the butyric acid sources used in this experiment would elicit different responses in pelleted nursery diets.
Keywords: butyric acid; growth; nursery pigs